Synthesis, characterisation and humidity sensing properties of PVA-NaI composite. (2022) - Singh, Arti; Singh, Pramod K.; Mathuriya, Abhilasha Singh; Sachdeva, Amit
Highlights: PVA-NaI based composite electrolyte has been synthesized using the solution casting method. The prepared composite was characterized by electrical and structural properties. Conductivity measurement of the composite was done using Complex Impedance Spectroscopy. The maximum conducting sample was further studied for its structural properties using X-Ray Diffraction. Perfect complexation between PVA and salt NaI was evaluated using Fourier transform Infrared Spectroscopy. Crystallinity or amorphicity of the maximum conducting sample was studied using X-Ray diffraction. The maximum conducting sample was used as a humidity sensor and surface properties were observed through Scanning Electron Microscopy. Abstract: PVA-NaI based composite electrolyte has been synthesized using the solution casting method. The prepared composite was characterized by electrical and structural properties. Conductivity measurement of the composite was done using Complex Impedance Spectroscopy. The maximum conducting sample was further studied for its structural properties using X-Ray Diffraction. Perfect complexation between PVA and salt NaI was evaluated using Fourier transform Infrared Spectroscopy. Crystallinity or amorphicity of the maximum conducting sample was studied using X-Ray diffraction. The maximum conducting sample was used as a humidity sensor and surface properties were observed through Scanning Electron Microscopy.